Pemetaan postingan facebook sebagai media promosi perpustakaan provinsi di Indonesia - Rini Oktaviani; Nining Sudiar; Hadira Latiar (FPPTI Jawa Tengah, 2022)
This research is entiled mapping facebook posts as a promotial media for provincipal libraries throught indonesia. The purpose of this study is to find out how to map facebook posts as a promotional media for provincial libraries throught Indonesia. The technique used in this research is descriptive quantitative approach. Statisticcollection strategies the usage of observation, documentation, literature look at, and interviews. The populace in this have a look at is 34 provinces and the pattern is 22 provinces. The result of this study were found in the provinces of Lampung and West Java with 353 posts, Bangka Belitung province with 288 posts, Riau province with 263 posts, Yogyakarta province with 143 posts, Jakarta province and West Kalimantan province with 141 posts. Of the nine indicators of the benefits of library promotion, the most posted are indicators that help inform library activities with the number of posts 1343 or (47.51%), indicators can help introduce existence with the number of posts 544 or (19.24%), indicators attract attention with the number of posts as many as 364 or (12.88%), the indicator helps tell about what is in the library with number of posts 242 or (8.56%), the indicator informs the new book with the number of posts 213 or (7,53%).